PECULIARITIES OF SPEECH USE SITUATIONS IN NATIVE LANGUAGE LESSONS AS A MEANS DEVELOPMENT OF COMMUNICATIVE COMPETENCE JUNIOR SCHOOLCHILDREN - І.А. Kravtsova (Academy of Cognitive and Natural Sciences, 2022)
The article investigates the problem of studying a native language basing on stududent, speech activity at the elementary level a special aftention is paid to didactic conditions while using comunicative competence skill, of young pupils.